1997
DOI: 10.1042/bj3230159
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bovine endothelial nitric oxide synthase as a homodimer with down-regulated uncoupled NADPH oxidase activity: tetrahydrobiopterin binding kinetics and role of haem in dimerization

Abstract: The fatty-acylation-deficient bovine endothelial NO synthase (eNOS) mutant (Gly-2 to Ala-2, G2AeNOS) was purified from a baculovirus overexpression system. The purified protein was soluble and highly active (0.2-0.7 micromol of l-citrulline. mg-1.min-1), contained 0. 77+/-0.01 equivalent of haem per subunit, showed a Soret maximum at 396 nm, and exhibited only minor uncoupling of NADPH oxidation in the absence of l-arginine or tetrahydrobiopterin. Radioligand binding studies revealed KD values of 147+/-24.1 nM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
109
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(120 citation statements)
references
References 59 publications
11
109
0
Order By: Relevance
“…As shown in the upper panel of Fig. 1, an anaerobic sample of ferric eNOS containing H4B displayed a broad Soret absorbance peak centered near 400 nm with flavin absorbance peaks ranging from 445 to 550 nm, consistent with earlier reports (8,9,23). Adding NADPH in the absence of bound CaM caused flavin reduction as judged by the disappearance of the flavin visible absorption bands.…”
Section: Extent and Kinetics Of Flavin And Hemesupporting
confidence: 75%
See 1 more Smart Citation
“…As shown in the upper panel of Fig. 1, an anaerobic sample of ferric eNOS containing H4B displayed a broad Soret absorbance peak centered near 400 nm with flavin absorbance peaks ranging from 445 to 550 nm, consistent with earlier reports (8,9,23). Adding NADPH in the absence of bound CaM caused flavin reduction as judged by the disappearance of the flavin visible absorption bands.…”
Section: Extent and Kinetics Of Flavin And Hemesupporting
confidence: 75%
“…A comparison of published steady-state rates shows that eNOS is about four to eight times slower than either nNOS or iNOS (7)(8)(9)(10)(11)(12)(13)(14). Because NO synthesis is actually the result of many steps, it is imperative to identify which steps limit the activity of a particular NOS isoform.…”
mentioning
confidence: 99%
“…Although the dissociation rate constants for BH 4 release from NOS at neutral pH are slow, reported as 0.01-0.3 min Ϫ1 (41)(42)(43), BH 4 release would likely be greatly accelerated under the acidotic conditions of the ischemic heart. Furthermore, oxidation of BH 4 can occur to both free and NOS-bound biopterin with rapid loss of BH 4 and XPH 2 formation (J.L.Z., R.B., W. Chen, and A.J.C., unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that dimerization is required for catalytic activity in all 3 NOS isoforms (1)(2)(3)(4)(5). The process of dimerization appears to depend on the presence of the cofactors heme and tetrahydrobiopterin as well as the enzyme sub-strate, L-arginine.…”
Section: Introductionmentioning
confidence: 99%